(untitled) (Configurazioni. Research on contemporary poetry, 2024)
The article opens with a reflection on poetry and criticism, considered not as two different types of textuality that articulate the form of the essay, thus an argument, but from the point of view of the value of thought that distinguishes writing as a hermeneutic form. Thus, an interpretation of Cristina Campo’s work is proposed, which allows the identification of two hermeneutic configurations (called recto and verso) of Italian poetry between the 1950s and 1960s. Campo reworks the latter with a lyrical meditation characterized by an original use of metaphor and the poetics of decreation, elements for rereading the history of twentieth-century lyric poetry.